Analisis atas Determinan Nilai Perusahaan dengan Struktur Modal sebagai Variabel Intervening - Sonya Dwi Listyani; Kurnia Heriansyah; Yetty Yetty Murni (Politeknik Keuangan Negara STAN, 2022)
This research aims to analyze and test empirical evidence of the effect of Profitability, Liquidity, Firm Size on Firm Value; the effect of Profitability, Liquidity, Company Size on Capital Structure; Effect of Capital Structure on Firm Value, and Capital Structure is able to mediate the effect of Profitability, Liquidity, Firm Size on Firm Value. The population of this study is all companies listed on the Indonesia Stock Exchange in 2016 – 2020. The sample determination includes companies listed on LQ45 non Banking. The analytical method used is the associative method, with classical assumption testing and path analysis. The results indicate that Profitability and Liquidity has a significant effect on Firm Value., Firm Size, and Capital Structure has an insignificant effect on Firm Value. Capital Structure is able to mediate Liquidity to Firm Value, and Capital Structure is not able to mediate Profitability and Firm Size to Firm Value.